Archaeococcoid scale insects (Hemiptera: Coccoidea) from the tropical high mountains of the Andean Cordillera, South America - Foldi, Imre (Zootaxa, 2009)
The diversity of the archaeococcoid scale insect fauna in the Cordillera of the Andes, particularly the páramos, was studied in Colombia, Ecuador, Peru, and Venezuela. The páramos is an ecosystem in the tropical high mountains, where the temperature alternates between freezing at night and thawing during the day. Within this habitat, two new genera and several new species and new country records were discovered and are described and illustrated below. Thus, at 4200 m in the Cordillera de Mérida, Venezuela, a new monophlebid genus, Corandesia Foldi n. gen., is erected for C. kozári Foldi n. sp. (Monophlebidae) based on the adult female. The genus Paramoandesia Foldi n. gen. (Monophlebidae) is erected for P. colombiensis Foldi n. sp. from 4200 m in Colombia, based on the adult female and male and for P. ecuadorensis Foldi n. sp. from 4100 m in Ecuador, based on the adult females. These three new species were found on Espeletia spp. (Asteraceae) in the páramos and, although living in the typically harsh environmental conditions of this habitat, do not appear to have developed special protective structures, although they have probably developed physiological adaptations and appear to exploit the protection afforded by the microhabitat at the base of large, dense leaves of their host plant. In addition, at 2000 m near Mérida, another monophlebid, Crypticerya abrahami (Newstead) was collected, previously only known from Guyana, and redescribed here based on the adult female and first-instar nymph. The adult and preadult females of Mimosicerya williamsi Foldi n. sp. (Coelostomidiidae) from 2500 m in Venezuela are described and illustrated. In addition, Platycoelostoma rauppi Foldi n. sp. (Callipappidae), a hypogeal species found on the roots of alfalfa in the mountains around Cusco, Peru, is described based on the adult female. This is the first record of a member of the Callipapidae from South America, as Platycoelostoma Morrison was previously believed to be restricted to Australia and to New Zealand. A taxonomic key to genera based on the adult females of Coelostomidiidae in the Neotropics is provided and, also keys to the adult females of species of Mimosicerya Cockerell (Coelostomidiidae), Paramoandesia (Monophlebidae) and to Platycoelostoma (Callipappidae).Les Archaeococcoides de la Cordillère des Andes de Colombie, de l’Equateur, du Pérou et du Venezuela sont analysés. Dans les páramos étudiés, un écosystème de haute montagne où les températures nuit-jour alternent entre congélation et décongélation, deux nouveau genres et plusieurs espèces nouvelles ont été découverts. Ainsi, dans les páramos de la Cordillère de Mérida, Venezuela, 4200 m, Corandesia Foldi n. gen. est créé pour l’espèce C. kozári Foldi n. sp. fondée sur l’adulte femelle. (Monophlebidae). Paramoandesia Foldi n. gen. est créé pour les espèces P. colombiensis Foldi n. sp. de Colombie, 4200 m, description fondée sur les adultes femelle et mâle et P. ecuadorensis Foldi n. sp. de l’Equateur, 4100 m, (Monophlebidae). Les espèces des páramos furent toutes collectées sur Espeletia spp. (Asteraceae) et, bien que vivant dans des conditions d’environnement extrêmes, elles n’ont cependant pas de structure de protection, mais ont développé probablement une adaptation physiologique, exploitent de plus l’effet protecteur du microclimat offert par les bases des larges feuilles de leurs plantes-hôtes. A une altitude inférieure près de Mérida au Venezuela, vers 2000 m, Crypticerya abrahami (Newstead) autre Monophlebidae, a été collectée, alors qu’elle n’était connue que de Guyana est redécrite fondée sur l’adulte femelle et de la première stade larvaire. Adulte et préadulte femelle de Mimosicerya williamsi Foldi n. sp. (Coelostomididae) du Venezuela, 2500 m, sont décrites et illustrées. Au Pérou, Platycoelostoma rauppi Foldi n. sp. (Callipappidae), espèce hypogée trouvée sur les racines de Medicago sativa, sur les montagnes environnantes de Cusco, décrite fondée sur l’adulte femelle. Il s’agit de la première découverte d’un membre de la famille des Callipappidae en Amérique du Sud, le genre Platycoelostoma Morrison étant jusqu’à présent considéré comme restreint à l’Australie et à la Nouvelle-Zélande. Une clef taxonomique fondée sur les adultes femelles est proposée pour les genres néotropicaux de Coelostomidiidae, ainsi que pour les espèces des genres Mimosicerya Cockerell (Coelostomidiidae), Paramoandesia (Monophlebidae), et Platycoelostoma Morrison (Callipappidae).